2023
DOI: 10.1186/s40168-023-01498-x
|View full text |Cite
|
Sign up to set email alerts
|

Core species and interactions prominent in fish-associated microbiome dynamics

Abstract: Background In aquatic ecosystems, the health and performance of fish depend greatly on the dynamics of microbial community structure in the background environment. Nonetheless, finding microbes with profound impacts on fish’s performance out of thousands of candidate species remains a major challenge. Methods We examined whether time-series analyses of microbial population dynamics could illuminate core components and structure of fish-associated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…In medicine, for example, the structure of human gut microbiomes varies considerably among host individuals, exhibiting complex associations with host human health [ 20 , 22 ]. Furthermore, recent studies have suggested that fish-associated and plant-associated microbiomes can be classified into several community compositional clusters potentially differing in physiological impacts on host organisms [ 14 , 63 ]. To extend the discussion on functional divergence of microbiomes, the genomic information of the microbes constituting microbiomes need to be enriched with shotgun metagenomic analyses [ 64-66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In medicine, for example, the structure of human gut microbiomes varies considerably among host individuals, exhibiting complex associations with host human health [ 20 , 22 ]. Furthermore, recent studies have suggested that fish-associated and plant-associated microbiomes can be classified into several community compositional clusters potentially differing in physiological impacts on host organisms [ 14 , 63 ]. To extend the discussion on functional divergence of microbiomes, the genomic information of the microbes constituting microbiomes need to be enriched with shotgun metagenomic analyses [ 64-66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because our present data lacked the information of temporal changes in community structure, we are unable to discuss the frequency and pace of community structural transitions between basins of attraction. Monitoring of microbiome compositions (Faust et al, 2015; Hayashi et al, 2024; Yajima et al, 2023) is necessary for filling the gap between theoretical and empirical studies (Long et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, these alternative gut microbiomes ("enterotypes") differ in their associations with human disease such as type II diabetes and Crohn's disease (Costea et al, 2017). In addition to those studies on animal-associated microbiomes (Arumugam et al, 2011;Moeller et al, 2012;Yajima et al, 2023), studies on plantassociated microbiomes have started to reorganize our recognition of how multistability of phyllosphere/rhizosphere microbiome structure is associated with ecosystem-scale processes and functions (Toju et al, 2018(Toju et al, , 2016. Because hundreds or thousands of replicate community samples are available in such microbiome studies, it is now possible to discuss potential relationship between community structure and ecosystem functions based on statistical signs of the presence of multiple basins (and background attractors).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the estimated concentrations of prokaryotic 16S rRNA and fungal ITS sequences in template DNA solutions ( 42 , 84 ), we calculated the ratio of prokaryotic DNA concentrations to fungal DNA concentrations in respective samples (prokaryote/fungus ratio) as follows:…”
Section: Methodsmentioning
confidence: 99%